Research on shoulder muscle strength feature of Chinese freestyle wrestlers - Dong, D.; Xu, L. W. (Journal of Chengdu Sport University, 2015)
Objective: the purpose of the paper is to discuss shoulder muscle strength feature of freestyle wrestlers in China. Methods: Through the ISOMED 2000 muscle testing system,the flexion,extension and rotation motion of the shoulder of male free wrestlers(12masters,9 good and 15 general ones) are analyzed. Results:( 1) The extensor is better than flexor muscle strength for different types of muscle and internal rotation is superior( P 0. 05).(2) The balance and stability strength in the static state(0o/ s) is good,but the stability in the fast state(180o/ s) is easy to be broken.( 3) There is significant difference between the PT / BW0o/ s,APT /BW0o/ s,AP180° / s,WF180° / sand other indicators of shoulder joint of different levels of athletes( P 0. 05).(4) there are significant features in H/Q0o/ s O / I0o/ s L / R0o/ s H / Q180° / sand other muscle strength indexes.Conclusion:(1) The stability strength of shoulder joint in dynamic conditions needs to be strengthened,especially the stability strength of fast state.(2) There is non-equilibrium in flexion,extension muscles or rotary internal,external muscles of shoulder joints. Sports injury can be avoided through strengthening balance training of shoulder joints.( 3) When wrestlers maximum strength has developed to a certain degree,priorities should be given to fast speed and endurance training because it might be more conducive to the improvement of sports performance.